ISAAC KALIMI, An Ancient Israelite Historian: Studies in the Chronicler, His Time, Place and Writing. Studia Semitica Neerlandica 46. Assen, Van Gorcum, 2005, 212 pp. ISBN 90-232-4071-5. U$D 138.00 - ISAAC KALIMI, The Reshaping of Ancient Israelite History in Chronicles. Winona Lake, Eisenbrauns, 2005, 473 pp. ISBN 1-57506-058-2. U$D 59.50 - Tebes, Juan Manuel (2010)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina; Argentina